OPTIC DISC PIT ASSOCIATED WITH CHOROIDAL COLOBOMA: CASE REPORT AND SHORT REVIEW - Jamil, Muhammad Usman; Mahmood, Aysal; Rizvi, Syed Fawad (Journal of Ayub Medical College Abbottabad, 2023)
Optic disc pits are hypothesized to form because of failure of embryonic fissure closure, which can also present with congenital defects in the choroid, RPE, and neurosensory retina. It is also associated with serous macular detachment. We present a case report of a 32-year-old man with an optic disc pit and independent choroidal coloboma below the inferior peripapillary area in the left eye, associated with macular retinoschisis with serous detachment.